Documentação na reserva técnica de arqueologia Mário Ferreira Simões, do Museu Paraense Emílio Goeldi: estudo de caso da coleção AM-IT-#: Médio Urubu - SALES, Taynara Soares do Nascimento (2019)
The museological documentation is a field of knowledge which includes techniques necessary for organization and communication of collected objects (collection) for research and then the public. Archaeology is a science that involves the registration of archaeological material and the relation between man and the material object (interpretation) in different periods and studies - in the pre-colonial period of the Amazon - the material culture of indigenous peoples deemed extinct, aiming to understand their meanings through extrinsic (spatial context) and intrinsic information in the object (shape, decoration, style, additives, etc.). Aiming at the importance of documentation of Projeto Arqueológico Médio Urubu (PMU - “Archaeological East Vulture Project”) (AM-IT-#) materials, present in the Mário Ferreira Simões Technical Reserve from the 1970s-1980s, proposing to integrate the existing information with new cataloging guidelines and inventory, this project aims to determine the potential of information of the most obvious sources for this research, which are the naturalist archaeologist Mario Simoes’ field reports. The researcher described each site excavated within PMU, as well as photographs, sketches of each site, location, dates, and other essential pieces of information, in the case of collection of archaeological materials. The research seeks to maximize and complement the materials information of the 43 excavated sites. The materials are stored in paper bags which contain the basic gathering information. The procedure performed was the creation of a label designed for documentary purposes and filled out with existing data and/or complementary information. The content of this research is important because it is the relation of the material/object/archaeological artifacts, and documentation and the link between the two research supports present in them, both the primary and the latest documentation. From this perspective the continuation of studies and museological techniques in archaeological context remains necessary for these procedures.